2007
DOI: 10.1002/eji.200636233
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccine encoding endosome‐targeted human papillomavirus type 16 E7 protein generates CD4+ T cell‐dependent protection

Abstract: Human papillomavirus type 16 is commonly implicated in cervical cancers. The viral genome encodes potential targets like the oncoprotein E7, expressed in transformed cells but thought to represent a poorly immunogenic antigen. We describe in this work a DNA-based vaccination protocol aimed at inducing an efficient anti-E7 immune response in vivo. Plasmids allowing the expression of the E7 protein in distinct cellular compartments were generated and assayed in an in vivo model of tumor growth. Our data demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…As a first step to test this, we confirmed that tethering to Ii chain significantly improved MHC class I-associated Ag presentation, as expected. With this information available, it was logical to go on and test whether Ii linkage might also induce protective CD8 + T cell immune responses in MHC class II-deficient hosts, although a previous study on the anticancer effect of an Ii-linked DNA vaccine pointed to an MHC class II dependence of protection (33). Our finding in this study, that only the adenoviral Ii-linked vaccine induced a potent CD8 + T cell response and robust short-term protection in MHC class II-deficient hosts, could support the assumption that a high level of Ag presentation on the vaccine vector-transduced cells, as is achieved with Ii linkage, in combination with innate signals induced through recognition of molecular patterns of the adenoviral vector, might act in concert to activate CD8 + T cells in the absence of CD4 + T cell help.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step to test this, we confirmed that tethering to Ii chain significantly improved MHC class I-associated Ag presentation, as expected. With this information available, it was logical to go on and test whether Ii linkage might also induce protective CD8 + T cell immune responses in MHC class II-deficient hosts, although a previous study on the anticancer effect of an Ii-linked DNA vaccine pointed to an MHC class II dependence of protection (33). Our finding in this study, that only the adenoviral Ii-linked vaccine induced a potent CD8 + T cell response and robust short-term protection in MHC class II-deficient hosts, could support the assumption that a high level of Ag presentation on the vaccine vector-transduced cells, as is achieved with Ii linkage, in combination with innate signals induced through recognition of molecular patterns of the adenoviral vector, might act in concert to activate CD8 + T cells in the absence of CD4 + T cell help.…”
Section: Discussionmentioning
confidence: 99%
“…Use of intracellular targeting strategies to the MHC class I and II processing pathways for enhanced antigen presentation by DCs [75][76][77][78][79] Codon optimization [80,81] Enhanced presentation of antigen through a MHC class I single chain trimer (SCT) composed of peptide, b2-microglobulin, and MHC class I heavy chain [82] Augmentation of DC and T cell interaction Inhibition of DC apoptosis [72,83] Promotion of in vivo DC expansion [84,85] Co-expression of cytokines and stimulatory molecules [76,86,87] Induction of helper T cell function [79] The DNA vaccine was well tolerated and a subset of the vaccinated patients who received the maximum dose of 4 mg of DNA/vaccination and a total of 4 vaccinations demonstrated detectable, systemic levels of E7-specific CD8+ T cell immune responses (Maura Gillison, personal communication).…”
Section: Humoral Mediated Antigen-specific Immunotherapymentioning
confidence: 99%
“…A number of studies suggest that vaccine-induced protection against TC-1 tumour is CD4 + cell independent Cheng et al, 2003;Loeser et al, 2007), 165 which was also the case with an E7-expressing tumour . However in some studies, CD4 + cells appear to play a role in tumour protection (Brulet et al, 2007;Park et al, 2008). Although both DCs and Langerhans cells can be directly cytopathic to tumour cells (Le Poole et al, 2008), the specific CD4 + subtype/s involved in TC-1 tumour protection have not as yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no vaccine which targets non-structural HPV antigens to provide protection against HPV-associated neoplasia, however animal models have demonstrated cell-mediated protection to be an efficacious strategy (Brulet et al, 2007;Daftarian et al, 2007;Haigh et al, 2007;Peng et al, 2008;Best et al, 2009;Chuang et al, 2009b;Yan et al, 2009). pE7HBE6 DNA vaccine shows great promise for use as a protective vaccine as well as a therapeutic agent, which would be cheap and stable and applicable to nations of all socio-economic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation